La máquina gubernamental. Soberanía y Gobierno en el pensamiento de Giorgio Agamben (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
The thesis of our essay is that in Agamben we could fin a conceptual displacement since the first book of his saga Homo sacer entitled Homo sacer I. Sovereign power and bare life in 1995, up to 2007 Homo sacer, II, 2, Il Regno e la Gloria. The nature of this displacement responds to the published Michel Foucault’s lectures of 1978 entiteled Security, Territory, Popula where, in Agamben’s view, the problem of gubernamentality posits as the condition of western sovereignity. That’s why Homo sacer saga suffers a radical inflection on its fundamental thesis: if in Homo sacer I. Sovereign power and bare life Agamben argues that sovereignity was the biopolitical paradigm of modernity in Homo sacer, II, 2, Il Regno e la Gloria Agamben argues that goverment and not sovereign, constitues that paradigm, it is what the italian philosopher calls the “gubernamental machine”.